2013
DOI: 10.1371/journal.pone.0083963
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Pathogen Induced Thaumatin-Like Protein Gene AdTLP from Arachis diogoi, a Wild Peanut

Abstract: Peanut (Arachis hypogaea L) is one of the widely cultivated and leading oilseed crops of the world and its yields are greatly affected by various biotic and abiotic stresses. Arachis diogoi, a wild relative of peanut, is an important source of genes for resistance against various stresses that affect peanut. In our previous study a thaumatin-like protein gene was found to be upregulated in a differential expression reverse transcription PCR (DDRT-PCR) study using the conidial spray of the late leaf spot pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 61 publications
2
94
1
3
Order By: Relevance
“…Concurrently, the up-regulation of thaumatin-like PR-5 during SA treatment was reported from Malus hupehensis [22], sorghum [130], wheat [155], Arachis diogoi [156] and Eucalyptus grandis [135].…”
Section: Discussionmentioning
confidence: 84%
“…Concurrently, the up-regulation of thaumatin-like PR-5 during SA treatment was reported from Malus hupehensis [22], sorghum [130], wheat [155], Arachis diogoi [156] and Eucalyptus grandis [135].…”
Section: Discussionmentioning
confidence: 84%
“…TLP have well described antifungal activity, causing osmotic breakage of transmembrane pores of the fungal plasma membranes [43]. Transgenic plants constitutively overexpressing TLPs often show enhanced fungal [44–48] and bacteria resistance [49]. Methyltransferase type 11 was one of the five most highly-expressed genes among the DEGs.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with our fi nding, Zamani et al (24) have reported that transgenic canola harboring rye tlp gene could inhibit the progress of the S. sclerotiorum fungal growth (24). The same fi ndings have also reported that overexpression of tlp gene demonstrates an inhibitory eff ect on phytopathogenic fungi through inhibition of the spore germination and mycelial growth (11,25,26).…”
Section: Discussionmentioning
confidence: 59%